2010
DOI: 10.1002/bmc.1454
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of oxyresveratrol analog trans‐2,4,3′,5′‐tetramethoxystilbene in rat plasma by a rapid HPLC method: application in a pre‐clinical pharmacokinetic study

Abstract: A rapid HPLC method was developed and validated for the quantification of oxyresveratrol analog trans-2,4,3',5'-tetramethoxystilbene (oxyresveratrol tetramethyl ether, OTE) in rat plasma. Chromatographic separation was achieved on an RP-HPLC column, which was protected by a guard column through a 12 min gradient delivery of a mixture of acetonitrile-water at 50°C. The UV absorbance at 325 nm was recorded. The retention time of OTE and trans-stilbene (internal standard) was about 7.7 and 8.4 min, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…The plasma half-life and metabolism of TMS is currently unknown, and whether TMS produces its effects directly and/or through one or more of its metabolites remains to be determined. Pharmacokinetic studies in rats have shown that TMS given intravenously as a bolus has a long terminal half-life and slow clearance rate (22). Although TMS has very low bioavailability (4.5%) when given by oral gavage to rats, plasma levels (85 ng/ml) obtained are far above its IC 50 (1.5 ng) to inhibit the activity of human recombinant CYP1B1 (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasma half-life and metabolism of TMS is currently unknown, and whether TMS produces its effects directly and/or through one or more of its metabolites remains to be determined. Pharmacokinetic studies in rats have shown that TMS given intravenously as a bolus has a long terminal half-life and slow clearance rate (22). Although TMS has very low bioavailability (4.5%) when given by oral gavage to rats, plasma levels (85 ng/ml) obtained are far above its IC 50 (1.5 ng) to inhibit the activity of human recombinant CYP1B1 (22).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic studies in rats have shown that TMS given intravenously as a bolus has a long terminal half-life and slow clearance rate (22). Although TMS has very low bioavailability (4.5%) when given by oral gavage to rats, plasma levels (85 ng/ml) obtained are far above its IC 50 (1.5 ng) to inhibit the activity of human recombinant CYP1B1 (22). That CYP1B1 contributes to the renal dysfunction associated with ANG II infusion is supported by our observation that CYP1B1 is expressed in the kidney and is localized in human kidneys in both the nucleus and cytoplasm of tubular cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…The chromatographic conditions were optimized by modifying the recent methods for quantification of various stilbenes in rat plasma [39]. The chromatographic separation was obtained by a reversed phase HPLC column (Agilent Zorbax Eclipse Plus C18: 250 × 4.6 mm i.d., 5 µm), which was protected by a guard column (Agilent Zorbax Eclipse Plus C18: 12.5 mm × 4.6 mm i.d., 5 µm) through a 12.5-min gradient delivery of a mixture of acetonitrile and water at a flow rate of 1.5 ml/min at 50 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The QC samples (14, 140 and 1400 ng/ml) were prepared and analyzed in the same way. The precision (RSD), accuracy (bias) and absolute recovery (%) were measured with the QC samples [3,5]. The stability of DFS under various conditions was assessed with the QC samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation